Efektivitas Model PBL terhadap Hasil Belajar Siswa pada Materi Ekosistem di SMA - Yuliani Sueng; Masdiana Sinambela (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
Education is a vital foundation for the development of high-quality human resources in an era of scientific and technological advancement. Therefore, the learning process in schools is expected to produce students who are active, innovative, and capable of solving problems in their daily lives. This study aims to determine the effectiveness of the Problem-Based Learning (PBL) model on student learning outcomes regarding ecosystem material at SMA Negeri 2 Percut Sei Tuan. This study employs a quantitative method using a One-Group Pretest-Posttest Design. The research sample consists of 36 students from class X-E, selected using random sampling. The research instruments consist of pretest and posttest questions to measure students’ cognitive learning outcomes. Data were analyzed using indicator achievement analysis, classical learning mastery, the Shapiro-Wilk normality test, the paired-sample t-test, and the N-Gain test. The results showed that classical learning mastery reached 100%, and 11 out of 12 learning indicators achieved mastery. The results of the hypothesis test showed a significance value of 0.000 < 0.05, so H₀ was rejected and Hₐ was accepted. The improvement in learning outcomes was also reinforced by an average N-Gain value of 0.7005, which falls into the high category, as well as an effectiveness rating of 70%, classified as “fairly effective”. These results indicate that the Problem Based Learning model is effective in improving students’ learning outcomes on ecosystem material.